PEMBERIAN ABU SEKAM DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) VARIETAS SERVO - Khoiruddin, Farit; Kurniastuti, Tri; Puspitorini, Palupi (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2018)
This study aims 1) This study aims to reveal the differences between the growth and yieldof tomato plants. 2) Knowing the difference between NPK fertilizer and the growth andyield of tomato plants. 3) Knowing the interaction between husk ash and NPK fertilizeron the growth and yield of tomato plants. This research was conducted using factorialrandomized block design (RCBD) with 2 factors, the first factor was husk ash (A)consisting of 3 levels, namely 50 g (A1), 60 g (A2), 70 g (A3) . The second factor is NPKfertilizer (P) consisting of 3 levels: 2.50 g (P1), 3.75 g (P2), 5 g (P3). Variables thatmention include plant height, number of leaves, time of flowering plants, number offruit plants and fruit weight. Analysis date using analysis of variance (ANOVA) level of5% and further testing with Duncan's Multiple Distance Test (DMRT). The resultsshowed that: There was no real interaction between rice husk ash fertilizer and NPKfertilizer on the growth and yield of tomato plants. Treatment of 70 g husk ash dose (A3)significantly affected plant height at the age of 14, 21, 28, and 42 HST. The treatment ofNPK fertilizer (P) is of real value for plant height, number of leaves and fruit weight.The best plant height was 52.18 cm and 84.06 at the age of 28 and 42 days afterplanting, the best number of leaves in puppol was 3.75 g (P2). But in people who aresweet, the yield is not significant.